The Role of E-Logistics and Blockchain-Based Logistics Networks in Improving Maritime Industry Logistics Performance - Lisda Rahmasari; Adenanthera L. Dewa; Widi Haryanti (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the influence of e-logistics and logistics networks on logistics performance, as well as to analyze the development project of blockchain technology adoption in mediating the relationship in the maritime industry. Quantitative methods are applied by collecting primary data through a questionnaire survey aimed at managers, staff, and employees of shipping companies in Semarang. Of the 300 questionnaires distributed, 231 were collected, but only 204 met the criteria for analysis using Structural Equation Modeling (SEM) with SmartPLS 4. The results of the study indicate that e-logistics has an influence on the adoption of blockchain technology but does not directly affect logistics performance. Conversely, logistics networks do not affect the adoption of blockchain technology but have a significant impact on logistics performance. The adoption of blockchain technology has a positive effect on logistics performance and serves as a mediator connecting e-logistics with logistics performance, although there is no significant influence between logistics networks and logistics performance through blockchain technology.